PENGEMBANGAN MEDIA KARTU KWARTET TEMA 9 SUBTEMA 1 DAN SUBTEMA 2 KELAS V SEKOLAH DASAR SWASTA - Fadli Surahman; Haidir; Dirneti; Erika; Eka Lenggang Dianasari (JURNAL MINDA, 2022)
This writing problem is lack of learning media used in schools makes students less active in learning, thus causing children not to pay attention to the teacher explaining and often disturbing friends next to them. This study aims to determine the feasibility of the quartet card media for Class V students. This type of research is development research with the Borg and Gall model, there are ten steps of development research, the trial subjects consisted of 2 material experts, design experts, 2 class V teachers at SDS 018 Plus Avicenna Indonesia, 4 grade V SDS 018 students. Plus Avicenna Indonesia for initialfield trials, 8 grade V SDS 018 Plus Avicenna Indonesia students for small group trials, 25 grade V students at SDS 018 Plus Avicenna Indonesia for large group trials. The results showed that: (1) validation of material experts based on eligibility according to the subcomponent as a whole was in the criteria of "very good / very feasible" (89%); (2) validation of media experts according to the aspects assessed as a whole is in the criteria of "very good / very feasible" (90%); (3) the class teacher validation is in the criteria of "very good / very feasible" (82%); (4) validation of initial field trials in accordance with the results of student responses who are assessed as a whole are in the criteria of "very good / very feasible" (88%); (5) small field trial validation is in the criteria of "very good / very feasible" (91%); (6) the validation of large field trials is considere as a whole to be in the criteria of "very good / very feasible" (93%)